On (f, I)-Lacunary Statistical Convergence of Order ? of Sequences of Sets - Sengul, Hacer; Et, Mikail; Cakalli, Huseyin (Soc Paranaense Matematica, 2020)
In this paper we introduce the concepts of Wijsman (f, I)-lacunary statistical convergence of order alpha and Wijsman strongly (f, I)-lacunary statistical convergence of order alpha, and investigated between their relationship.
Keywords: I-convergence; Wijsman statistical convergence; Lacunary sequence